Accuracy Analysis of Two Parallel Manipulators - Hajdu, Sándor; Bodnár, Dávid (International Journal of Engineering and Management Sciences, 2019)
The aim of the study is to analyse and visualize the accuracy of two parallel manipulators. The kinematics are calculated using vectors and the Newton method. The accuracy is calculated based on the actuator errors, visualization is done with color shading. Calculations was done using MATLAB